A study of interventions and their outcome in the management of acute pancreatitis - Viswanath, Muppa; R., Rakesh; Kunnuru, Supreeth Kumar Reddy; Perubhotla, Raghu Sri Charan; Gurjar, Mayank Kumar; Varty, Gurudutt P.; Desu, Bharath Kumar; Salavakam, Muni Krishna; S., Thirunavukkarasu (International Surgery Journal, 2019)
Background: Acute pancreatitis is the most terrible of all the calamities that occur in connection with the abdominal viscera. The suddenness of its onset, the illimitable agony which accompanies it, and the mortality attendant upon it, all render it the most formidable of catastrophes. Aim of the study is to evaluate the treatment outcome in acute pancreatitis. Methods: All the patients who underwent surgery for chronic pancreatitis were included in the study. initial APACHE II score at admission and CT severity index was evaluated. Results: Edematous pancreatitis accounts for 80–90% of acute pancreatitis and remission can be achieved in most of the patients without receiving any special treatment. Necrotizing pancreatitis occupies 10–20% of acute pancreatitis and the mortality rate is reported to be 14-25%. Alcohol (45.8%) was the most common causes of acute severe pancreatitis in this study. Males were predominately affected (Male: Female = 29:5). Complication rate or morbidity is 50%. The initial APACHE II score at admission and CT severity index in the first scan were high in patients who underwent necrosectomy and the patients who died. The overall mortality in this study was 30.6%. Conclusions: In conclusion, one reason attributed to high mortality was due to the subgroup of patients who underwent PCD alone and failed to show any change in the recovery nor deterioration and lead to gross nutritional depletion and death, secondly those patients who underwent step up approach and ultimately needed surgery have more aggressive disease evidenced by high APACHE II score, CT severity index and % of necrosis.